Hymenolepidid Cestodes from Grebes (Aves, Podicipedidae) in Ukraine: the Genus Confluaria - Vasileva, G.P.; Kornyushin, V.V.; Genov, T. (Вестник зоологии, 2001)
Redescriptions of 5 species of the hymenolepidid cestodes from the genus Confluaria Ablasov in Spasskaja, 1966 recorded from grebes (Podicipedidae) in Ukraine are presented: Confluaria podicipina from Podiceps nigricollis; Confluaria furcifera from P. grisegena, P. cristatus and P. nigricollis; Confluaria pseudofurcifera (new geographical record) from P. cristatus; Confluaria capillaris from P. grisegena and P. nigricollis; Confluaria multistriata from Tachybaptus ruficollis. Confluaria krabbei sp. n. from T. ruficollis is described. It is differentiated from C. multistriata by possessing rostellar hooks with epiphyseal thickenings comprising both handle and guard and by the shorter cirrus-sac which does not reach the mid-line of the proglottis.